The Effect of Learning Styles on Vocabulary Mastery among Second-Year Students - Pratiwi, Alifiah; Suryadi, Ray; Astiantih , Susi; Sultan; Putra, Eko; Syahria, Nur; Naing, Ince Rezky (LifeSciFi, 2025)
This study investigates the relationship between students’ learning styles and vocabulary achievement among second-grade students at Public Junior High School of 6 Buton Tengah. Employing a correlational research design, data were collected through a learning style questionnaire (covering visual, auditory, and kinesthetic preferences) and a vocabulary achievement test. The sample consisted of 25 students from Class C. Data analysis was conducted using the Pearson Product-Moment correlation formula. The findings reveal a significant positive correlation between each learning style and vocabulary achievement, with correlation coefficients of r = 0.838 for visual, r = 1.000 for auditory, and r = 0.923 for kinesthetic learning styles. These results indicate that students' preferred learning styles strongly influence their vocabulary mastery. The study highlights the importance for educators to recognize and integrate diverse learning styles in instructional strategies to enhance vocabulary acquisition. Future research is recommended to involve a larger and more diverse sample to generalize findings and explore causal relationships.